PupilEXT: Flexible Open-Source Platform for High-Resolution Pupillometry in Vision Research - Zandi, Babak; Lode, Moritz; Herzog, Alexander; Sakas, Georgios; Khanh, Tran Quoc (Frontiers in Neuroscience, 2021)
The human pupil behaviour has gained increased attention due to the discovery of the intrinsically photosensitive ganglion cells and the afferent pupil control path’s role as a biomarker for cognitive processes. Diameter changes in the range of 10-2 mm are of interest, requiring reliable and characterized measurement equipment to detect neurocognitive effects on the pupil accurately. Mostly commercial solutions are used as measurement devices in pupillometry, associated with high investments. Moreover, commercial systems rely on closed software, restricting conclusions about the used pupil tracking algorithms. Here, we developed an open-source pupillometry platform consisting of hard- and software competitive with high-end commercial stereo eye-tracking systems. Our goal was to make a professional remote pupil measurement pipeline for laboratory conditions accessible for everyone. This work’s core outcome is an integrated cross-platform (macOS, Windows, Linux) pupillometry software called PupilEXT, featuring a user-friendly graphical interface covering the relevant requirements of professional pupil response research. We offer a selection of six state-of-the-art open-source pupil detection algorithms (Starburst, Swirski, ExCuSe, ElSe, PuRe, PuReST) to perform the pupil measurement. A developed 120 fps pupillometry demo system was able to achieve a calibration accuracy of 0.003 mm and an averaged temporal pupil measurement detection accuracy of 0.0059 mm in stereo mode. The PupilEXT software has extended features in pupil detection, measurement validation, image acquisition, data acquisition, offline pupil measurement, camera calibration, stereo vision, data visualization and system independence, all combined in a single open-source interface, available at https://github.com/openPupil/Open-PupilEXT.